Plant components can reduce methylmercury toxication: A mini-review - Chang, Jie; Zhou, Yun; Wang, Qiang; Aschner, Michael; Lu, Rongzhu (Biochimica et biophysica acta. General subjects, 2019)
Methylmercury (MeHg) is a ubiquitous environmental pollutant, with the nervous system as its main target; however, the neurotoxic mechanisms of MeHg have not been fully elucidated, and no effective therapeutic and preventive drugs are available to mitigate its toxicity. Recent evidence suggests a reduction in the toxicity of MeHg by natural plant extracts. The aim of this review is to provide an overview of effective natural plant extracts and their putative biochemical mechanisms for blocking gut absorption, enhancing excretion and minimizing toxic effects of MeHg. Natural plant extracts may act as potential therapeutics in response to MeHg exposure. The roles plant components play in the reduction of MeHg toxicity may be multifaceted including: (1) attenuating neurobehavioral deficits; (2) facilitating demethylation of MeHg to inorganic mercury; (3) reducing MeHg absorption from the gastrointestinal tract; (4) redistributing MeHg to less sensitive target organs and tissues; (5) promoting enterohepatic circulation of MeHg to increase its biliary and intestinal excretion; (6) restoring intracellular redox status. The possible protective effects of natural plant components contribute to the understanding of mechanisms of MeHg toxicity and to the development of novel therapeutic strategies. •The roles of plant components in the reduction of MeHg toxicity are multifaceted.•Plant components reduce MeHg absorption from gut and increase its biliary and intestinal excretion.•Plant components facilitate the functional recovery from damage by MeHg.